A Review of The Reader Response Notebook: Teaching toward Agency, Autonomy, and Accountability - Bobbie Kabuto (Networks: An Online Journal for Teacher Research, 2020)
This book review examines two overlapping narratives in Ted Kelser’s The Reader Response Notebook: Teaching toward Agency, Autonomy, and Accountability. The first narrative is the reflective professional journey of Ted Kesler, who began re-envisioning the possibilities of reader response notebooks while he was an elementary and middle school teacher in New York City Public Schools. The second narrative is that of the students who used reader response notebooks in their classrooms. This review concludes with the idea of how The Reader Response Notebook is a comprehensive, practical book for teachers. The Reader Response Notebook exemplifies how inquiry lead to action to improve student learning through introspective and reflective thinking from classroom teachers and students.
Keywords: Reading Response Notebooks; Classroom-Based Inquiry